2009
DOI: 10.1108/17506120910948494
|View full text |Cite
|
Sign up to set email alerts
|

Development of a service quality scale for pharmaceutical supply chains

Abstract: Purpose -To develop a scale for the measurement of service quality in pharmaceutical supply chains.Methodology / approach -413 pharmaceutical retailers working in the 2 biggest cities of Pakistan responded to a survey. Confirmatory factor analysis developed a valid and reliable service quality measurement scale with 4 dimensions and 10 items.Findings -Findings of this research are consistent with other service quality studies.There is no universal set of dimensions and items that determine service quality acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 49 publications
(75 reference statements)
3
14
0
Order By: Relevance
“…Thus, the study has proposed a new scale, using inputs from literature and practitioners of small-medium manufacturing enterprises. The findings of this study are in alignment with those obtained by Ahmad et al (2009); Rodrigues et al (2011);Prakash (2014) and Parmata (2016). The proposed model embodies relationship among variables defined to co-create value for both provider and receiver and suggests facilitate planning and implementing of quality improvement programs towards the appraisal and performance evaluation of HR function in the organizations under study.…”
Section: Resultssupporting
confidence: 78%
“…Thus, the study has proposed a new scale, using inputs from literature and practitioners of small-medium manufacturing enterprises. The findings of this study are in alignment with those obtained by Ahmad et al (2009); Rodrigues et al (2011);Prakash (2014) and Parmata (2016). The proposed model embodies relationship among variables defined to co-create value for both provider and receiver and suggests facilitate planning and implementing of quality improvement programs towards the appraisal and performance evaluation of HR function in the organizations under study.…”
Section: Resultssupporting
confidence: 78%
“…Other studies conducted in emerging economies have reported similar issues (e.g. Ahmad et al, 2009;Ali et al, 2012;Dubey & Gunasekaran, 2016;Jeswani et al, 2008;Kureshi et al, 2010;Ryan & Tipu, 2013;Singh et al, 2010). For example, Malik and Kotabe (2009) collected data from seven cities in India and Pakistan using convenience sampling, and could not find an up-to-date list of firms operating in each country.…”
Section: Data Collection Methodsmentioning
confidence: 94%
“…The companies in capital have the potential to lobby to influence the MOH and Food and Drug Organization. [ 19 20 21 ]…”
Section: Discussionmentioning
confidence: 99%